Poder de mercado e rentabilidade das empresas brasileiras listadas em bolsa - Fonseca, Andrew Machado (Universidade do Vale do Rio dos Sinos, 2024)
This monograph investigates the market power and profitability of companies involved in the Brazilian stock exchange, Brasil, Bolsa e Balcão - B3 for a time frame between the periods of 2016 and 2022. To understand these characteristics, the present study sought to demonstrate the concepts of Lerner and Markup index through an economic perspective. Through an analysis using the Almost Ideal Demand – AIDS assessment method, it was possible to estimate companies' pseudo prices and compensated price specifications. Looking specifically at the financial sector. The results demonstrated that the relationship between financial sectors is highly technical and price specifications can vary and be complex depending on the context. This may result in lower price elasticity, as these companies may be able to dictate prices without suffering a significant loss of market share. The analysis also highlighted practical and theoretical implications regarding the consequences of market monopolies. This dissertation contributes to the existing literature and concludes that the initial market logic and profitability for companies in periods of expansion of economic activity, in highly concentrated sectors can experience an increase in their market shares as the developed conditions allow them to grow faster than its smaller competitors. This can lead to greater market concentration during boom times. It is hoped that this study will promote a greater and deeper understanding of the research problem and inspire future research in the area.
Keywords: Markup; Ciclos econômicos; Elasticidade; índice Lerner; Economic cycles; Elasticity; Lerner index; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis